Master curve approach to monitor fracture toughness of reactor pressure vessels in nuclear power plants. - Kang, K. S.; Kupca, L. (International Atomic Energy Agency, 2009)
This publication provides information about the master curve approach for assessing the structural integrity of reactor pressure vessels (RPVs) under current and future operation and accident conditions in nuclear power plants (NPPs). This direct measurement of fracture toughness approach is technically superior to the correlative and indirect methods used in the past to assess irradiated RPV integrity. The results in the report should allow utility engineers and scientists to directly measure fracture toughness using small surveillance sized specimens and apply the results using the master curve approach for RPV structural integrity assessment in NPPs.--Publisher's description.
"October 2009."
"The IAEA officers responsible for this publication were K.S. Kang and L. Kupca of the Division of Nuclear Power"--PDF Foreword page.
Keywords: Nuclear pressure vessels -- Materials -- Effect of radiation on.; Nuclear pressure vessels -- Materials -- Fracture.; Nuclear pressure vessels -- Materials -- Embrittlement.; Nuclear pressure vessels -- Materials -- Testing.; Nuclear power plants -- Materials -- Effect of radiation on.; elektronické knihy; electronic books